Measurement invariance across age, gender, ethnicity, and psychopathology of the Psychotic‐Like Experiences Questionnaire for Children in a community sample - Piltz, Lauren M.; Carpendale, Emma J.; Laurens, Kristin R. (International journal of methods in psychiatric research, 2023)
Objectives The current study aimed to assess the measurement invariance of the 9‐item self‐report Psychotic‐Like Experiences Questionnaire for Children (PLEQ‐C) across various demographic (age, gender, ethnicity) and psychopathology profiles in a community sample of children. Methods Children aged 9–11 years (n = 613; M age = 10.4 years [SD = 0.8]; 50.9% female) completed questionnaire screening at school, with primary caregivers returning questionnaires by mail from home. Configural, metric, scalar, and residual invariance of the PLEQ‐C scores were investigated across groups differentiated by age (9; 10; 11 years), gender (female; male), ethnicity (white; black; other), and by child‐reported and caregiver‐reported psychopathology (abnormal rating; not abnormal). Results The PLEQ‐C scores demonstrated good unidimensional model fit. Full configural, metric, scalar, and residual invariance were demonstrated across gender, ethnicity, and psychopathology (both child‐ and caregiver‐reported). Across age groups, the PLEQ‐C scores showed full configural and metric invariance, but only partial scalar and residual invariance (with a single item measuring differently among 11‐year‐olds). Conclusions In this community sample, the PLEQ‐C was robust to age, gender, ethnicity, and psychopathology profiles, providing evidence of its capacity to identify children in the general population who might benefit from further assessment to determine the clinical significance of their psychotic experiences.